0475 Reducing Dysfunctional Sleep-Related Cognitions Improves Nighttime Sleep and Daytime Consequences in Older Adults with Insomnia. (27th May 2020) - Song, Y; Kelly, M R; Fung, C H; Dzierzewski, J M; Grinberg, A; Mitchell, M N; Josephson, K; Fiorentino, L; Martin, J L; Alessi, C A
Abstract: Introduction: The long-term impact of addressing sleep-related cognitions, which is an important component of cognitive behavioral therapy for insomnia (CBTI), has not been established, particularly in older adults. We examined whether specific changes in sleep-related cognitions predicted long-term changes in sleep and other outcomes following CBTI in older adults. Methods: We analyzed data from a randomized controlled trial testing CBTI in older veterans with insomnia (N=159, mean age 72 years). Sleep-related cognitions were assessed with the Dysfunctional Beliefs and Attitudes about Sleep scale (DBAS, subscales: Consequences, Worry/Helplessness, Sleep Expectations, Medication). Outcome measures included the Pittsburgh Sleep Quality Index (PSQI), Insomnia Severity Index (ISI), Epworth Sleepiness Scale (ESS), sleep diary variables, Flinders Fatigue Scale (FFS), and Short Form-12 health-related quality of life (QOL). Analyses completed slope of change in DBAS subscales (baseline to post-treatment: T1) between CBTI and control with respect to slope of change in sleep and other outcomes from post-treatment to 6-months (T2). Results: Compared to controls, the CBTI group had significantly stronger associations between improvement (T1) in DBAS-Consequences and subsequent (T2) improvement in PSQI (difference in slopes [DIS]=0.9, 95%CI=[.29, 1.43], p=0.004), ISI (DIS=1.1, 95%CI=[.18, 2.0], p=0.019), ESS (DIS=0.6, 95%CI=[.10, 1.18], p=0.020), and FFS (DIS=1.9, 95%CI=[.76, 3.09], p=0.001). The CBTI group also had significantly stronger associations between improvement in DBAS-Worry/Helplessness and subsequent improvements in PSQI, ISI, and FFS; improvement in DBAS-Medication and PSQI and ISI; and improvement in DBAS-Sleep Expectations and improved FFS. Slopes were not different between groups for sleep diary variables or QOL. Conclusion: Significant improvements in sleep-related cognitions with CBTI across DBAS subscales in older adults predicted improvement in several outcomes of nighttime sleep and daytime consequences. These findings suggest the importance of addressing dysfunctional sleep-related cognitions for sustained improvement with CBTI in older adults Support: The study was supported by VA Health Services, Research and Development (Alessi, IIR 08-295), National Institute on Aging (K23AG055668, Song), National Heart, Lung, and Blood Institute (K24HL 143055, Martin) of the National Institutes of Health and VA Greater Los Angeles Healthcare System, Geriatric Research, Education and Clinical Center.